SET TO SET BROADCASTING IN COMMUNICATION-NETWORKS - LEE, HM; CHANG, GJ (My University, 1992)
Suppose G = (V,E) is a graph whose vertices represent people and edges represent telephone lines between pairs of people. Each person knows a unique message and is ignorant of the messages of other people at the beginning. These messages are then spread by telephone calls. In each call, two people exchange all information they have so far in exactly one unit of time. Suppose A and B are two nonempty subsets of V. The main purpose of this paper is to study the minimum number b(A,B,G) of telephone calls by which A broadcasts to B; and the minimum time t(A,B,G) such that A broadcasts to B. In particular, we give an exact formula for b(A,B,K(n)) and linear-time algorithms for computing b(A,B,T) and t(A,B,T) of a tree T.
Keywords: GOSSIP; BROADCAST; COMPLETE GRAPH; TREE; ALGORITHM